Os gêneros no livro didático de língua portuguesa das telessalas do Projeto Travessia - Pinto, Aldeniz dos Santos (2009)
This work is addressed to a search about textual genres from a L.D textbook. From a virtualroom in a state School of Pernambuco with interest to analyse specifically the balance between the thematic (cenatextos), the genres and the activities proposed in the LD and within this purpose, it was based mainly on Bronckart (2003), Dolz and Sheneuwly (2004), Soares (2004). Two points are examining, qualitatively and quantitatively, from the three volumes reached it was developed the said textbook and 160 (one hundred and sixty) questionnaires in order to check also whether the teachers enjoyed the searched LD or not. This L.D confirms the theories sociocomunications from genres and the notion of literacy, it also offers students the possibility to be in contact with the heterogeneity and not only with some genres considered to be scholar ones, which make education homogeneous, preferences and particularities of each student. Exploring genres in the activities of reading and production, it explores the issue of diversity genres. In addition, there is an emphasis on literary texts and connecting the practice of communicative approach daily. In relation to the connection established between the thematic and activities included in the LD, the final result reached the interconnection shows that it is mostly quite harmonious. The percentage of the questionnaire indicates that most of teachers, received it assess and positively.